Trace Metal Levels of Some Medical and Aromatic Plants Collected from High Density Traffic Areas in Tokat, Turkey - Koc, Huseyin; Mendil, Durali; Tuzen, Mustafa; Sari, Hayati; Hasdemir, Erdogan (Asian Journal of Chemistry, 2016)
The aim of this work was to determine the trace metal levels in some medical and aromatic plants growing on high traffic density areas. Eight species of medical and aromatic plant samples were collected from near the Tokat-Ankara motorway in Turkey. Six trace metals (Fe, Mn, Zn, Ph, Ni and Cu) in the samples were analyzed using flame and graphite furnace atomic absorption spectrometry after microwave digestion. The metal concentrations in samples were found to be 365-90, 55-14, 33.72-1.36, 3.10-1.98, 6.39-1.22 and 11.73-7.03 μg/g for iron, manganese, zinc, lead, nickel and copper, respectively. Trace metal concentrations in samples were found below the toxic levels.